Cooperation against all predictions - Friedel Bolle; Jörg Spiller (Economic Inquiry, 2021)
In Binary Threshold Public Good (BTPG) games, n players have binary choices: cooperation or non-cooperation. If at least k players cooperate, a public good is produced. The case k = n is the Stag Hunt game with the two pure strategy equilibria E1 (all players cooperate) and E0 (no player cooperates). In four rather diverse examples of four-player Stag Hunt games, three prominent concepts of equilibrium selection favor E0. Experiments, however, result in cooperation frequencies between 70.3% and 99.7%. Also for k < n, the selected equilibria clearly differ from experimental behavior. We interpret our observations by suggesting the concept Behavioral Equilibrium Selection.
Keywords: 330; equilibrium selection; experiments; global games; payoff dominance; quantal response equilibria; risk dominance; Stag Hunt games